Biodegradation of polyurethane derived from castor oil - Cangemi,José M. (2008)
The aim of this research was to study the biodegradation of a polymer derived from castor oil, which is a renewable, natural material that is a practical alternative for the replacement of traditional polyurethane foams. Due to its molecular structure, which contains polyester segments derived from vegetable oil, the polymeric surface is susceptible to microorganism attack. This study tested the biological degrading agent that was in contact with the microorganisms resulting from microbiological grease degrading agents, when foam was inoculated. Solid-media agar-plate tests were conducted for their potential to evaluate the biodegradation of polymeric particles by specific strains of microorganisms during 216 hours. The growth rate was defined. This technique provides a way of distinguishing the degradation abilities of microorganisms from the degradability of materials.